2017
DOI: 10.1177/0021998317692655
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior of double-edge notched oxide/oxide ceramic matrix composite in a combustion environment

Abstract: Tension–tension fatigue tests in a combustion environment were performed on double-edge notched oxide/oxide ceramic matrix composite specimens. The composite, designated as N720/A, constituted woven 0°/90° Nextel™720 fibers in alumina matrix. Monotonic tensile and cyclic loads at a frequency of 1 Hz and a stress ratio of 0.05 were applied on the specimens in a combustion environment. The maximum specimen temperature due to combustion flame impingement in the notch region was 1250 ± 50℃. A stiffness reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…This first and foremost shows that the harsh combustion environment had negligible effect on the material degradation. A similar conclusion was reached in an earlier study by Singh et al where it was shown that thermal gradient stresses rather than environmental degradation due to the harsh combustion environment influenced the strength and life of CMCs in combustion environment. In the present study, the stiffness reduction being directly proportional to the applied maximum stress supports micro level damage due to mechanical loadings being the prime cause of material degradation and subsequent catastrophic failure.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…This first and foremost shows that the harsh combustion environment had negligible effect on the material degradation. A similar conclusion was reached in an earlier study by Singh et al where it was shown that thermal gradient stresses rather than environmental degradation due to the harsh combustion environment influenced the strength and life of CMCs in combustion environment. In the present study, the stiffness reduction being directly proportional to the applied maximum stress supports micro level damage due to mechanical loadings being the prime cause of material degradation and subsequent catastrophic failure.…”
Section: Resultsmentioning
confidence: 96%
“…An earlier work by Singh et al uses finite element method to investigate the effects of thermal gradient stresses on the strength and life of notched Oxide/Oxide CMCs in essentially the same combustion environment. Those evaluations were deemed essential in that particular research, so that the strength and fatigue life comparisons could be made between combustion and elevated temperature “isothermal” laboratory air environment. It was shown that the presence of thermal gradient stresses resulted in significantly lower tensile strength and fatigue life in combustion environment in comparison to isothermal laboratory air environment .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations